Online Al-Qur’an learning for adult asnaf-mualaf: analysis of issues for recommendation - Aliff Nawi; Mohd Faiz Mohd Yaakob; Nor Yazi Khamis; Wan Hilmi Wan Abdullah; Mohd Adil Mustaffa; Fatin Athirah Zameran (Journal of Education and Learning (EduLearn), 2026)
Since the COVID-19 pandemic, there has been a hitch in Qur’an education, signalling a need to shift to online learning. When the Islamic learning centres ceased to operate due to the lockdown, adult asnaf-mualaf (reverts who are eligible to receive zakat or other forms of Islamic aids) were held back from physically attending Al-Qur’an lessons. The measure has disrupted their ongoing learning of the Qur’an, and prolonged disruption is feared to cause disengagement among the asnaf. Hence, this study arranged five meetings over three weeks for online Qur’an lessons, each lasting an hour, for eight asnaf-mualaf. A qualitative exploration of the online lessons was conducted to determine suitable mechanisms, issues, and challenges faced by the asnaf in online Qur’an learning. Interview protocol refinement (IPR) was employed to ensure the method was executed ethically, and the data were coded and analysed thematically using ATLAS.ti. The findings revealed a preference for WhatsApp, while low internet quality and accessibility were the expected apparent challenges during the restriction. The study underscores the importance of catering to the participants’ needs and addressing their lack, indicating a shift towards an andragogical approach of learner-centredness. Several actionable recommendations are forwarded to enhance the online Qur’an instructions for asnaf-mualaf.